2023
DOI: 10.3390/biomimetics8050436
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving like a Bat: Hierarchical 3D Geometric–Semantic Scene Understanding Inspired by a Biomimetic Mechanism

Chi Zhang,
Zhong Yang,
Bayang Xue
et al.

Abstract: Geometric–semantic scene understanding is a spatial intelligence capability that is essential for robots to perceive and navigate the world. However, understanding a natural scene remains challenging for robots because of restricted sensors and time-varying situations. In contrast, humans and animals are able to form a complex neuromorphic concept of the scene they move in. This neuromorphic concept captures geometric and semantic aspects of the scenario and reconstructs the scene at multiple levels of abstrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…While it has been observed that bats can predict aspects of the scene by accumulating sensor data [60], to the best of our knowledge, no concrete model on how this prediction might operate has been proposed in previous works. Other technical systems have been proposed to produce 3D scene reconstruction and semantic interpretation, [61], [62], but these proposed techniques utilize a teaching modality like LIDARs or cameras to perform a form of modality translation. Our SonoNERF model relies solely on acoustic data without the need for an additional supervision modality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it has been observed that bats can predict aspects of the scene by accumulating sensor data [60], to the best of our knowledge, no concrete model on how this prediction might operate has been proposed in previous works. Other technical systems have been proposed to produce 3D scene reconstruction and semantic interpretation, [61], [62], but these proposed techniques utilize a teaching modality like LIDARs or cameras to perform a form of modality translation. Our SonoNERF model relies solely on acoustic data without the need for an additional supervision modality.…”
Section: Discussionmentioning
confidence: 99%
“…Our SonoNERF model relies solely on acoustic data without the need for an additional supervision modality. Furthermore, reference [62] does not use an acoustic sensing modality, causing the title to be somewhat misleading. Our approach follows the approach called ‘self-supervised learning’ which has received much attention in the recent years [63], [64].…”
Section: Discussionmentioning
confidence: 99%
“…What, in the opinion of the authors, is not so trivial is the fact that 3D scene reconstruction emerges when solving a completely different task, namely predicting sensor data for a novel scene, and whereas it has been observed that bats can predict aspects of the scene by accumulating sensor data [ 58 ], to the best of our knowledge, no concrete model on how this prediction might operate has been proposed in previous works. Other technical systems have been proposed to produce 3D scene reconstruction and semantic interpretation [ 59 , 60 ], but these proposed techniques utilize a teaching modality like LIDARs or cameras to perform a form of modality translation. Our SonoNERF model relies solely on acoustic data without the need for an additional supervision modality.…”
Section: Discussion and Conclusionmentioning
confidence: 99%
“…Our SonoNERF model relies solely on acoustic data without the need for an additional supervision modality. Furthermore, reference [ 60 ] does not use an acoustic sensing modality, causing the title to be somewhat misleading. Our approach follows the approach called ‘self-supervised learning’, which has received much attention in recent years [ 61 , 62 ].…”
Section: Discussion and Conclusionmentioning
confidence: 99%